Near constant discharge performance analysis of a dual accumulator configuration quasi-isothermal compressed gas energy storage based on condensable gas. (December 2020) - Zhao, Pan; Lai, Yongquan; Zhang, Shiqiang; Xu, Wenpan; Wang, Jiangfeng; Dai, Yiping
Highlights: A quasi-isothermal compressed gas energy storage based condensable gas is proposed. The dual accumulator and gas phase change to realize near constant discharge. The transient model is conducted to analyze the thermodynamic performance. The parametric analysis is studied and the off-design performance is predicted. Abstract: Energy storage can provide flexibility on both power generation and consumption sides when large renewables penetrate, leading to a low-carbon society development. Although the compressed air energy storage (CAES) system usually emerges as a grid-scale energy storage facility, the small-scale CAES system, especially isothermal or quasi-isothermal CAES, with constant or near constant power output may be effective to provide urgent power for special load in some other occasions. Meanwhile, the isobaric process can be enlightened by the phase change of condensable gas at its saturation pressure. From this viewpoint, the near constant discharge performance analysis of a dual hydraulic accumulator configuration quasi-isothermal compressed gas energy storage based on condensable gas R41 is proposed in this paper. The methods of liquid piston and spraying liquid are adopted to realize a quasi-isothermal process. The phase change of condensable gas at saturation pressure and dual accumulator configuration are two measures to maintain the gas pressure lay in a narrow range, implying a near constant discharge. Based on the system transient model, the transient analysis of system components, parametric analysis, off-design analysis and variant system performance analysis are conducted. Results show that the system round trip efficiency (RTE) and energy density (ED) are 63.98% and 0.1175 kWh/m 3, respectively. The power output is located in the range from 0.93 kW to 1.11 kW, which is relatively stable and around the 1 kW rated power. Moreover, the initial quality of R41 and volume of accumulator have effect on system performance. Meanwhile, the Pelton turbine power level can be adjusted by altering jets number and nozzle effective area.